Small aperture radial line slot array antenna design and development for indoor wireless local area network application - 327573 Farah Ayu Ismail Kassim (Skudai : Universiti Teknologi Malaysia, 2004)
Thesis (Sarjana Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2004